Evaluation of student performance in laboratory applications using fuzzy decision support system model - (:unkn) unknown (IEEE Computer Society, 2014)
In recent years, the importance of laboratory applications in engineering education has increased because, there is need for transferring the theoretical knowledge to empirical research and practice, which is particularly significant for the development of students in their career. Therefore, the evaluation of these laboratory applications should be effective. In this study, we propose a new approach to this assessment system. Our approach uses fuzzy decision support system and proposes a new approach that is called 'refinement process' on student grades. Fuzzy helps more reliable decision making and evaluation of applications using a pre-determined list of criteria. This model based on fuzzy multi criteria method, is developed for evaluating student performances in laboratory activities which consolidate theoretical knowledge with practical applications. In our approach, we use peer assessment, group assessment and personal assessment methods. This study shows that fuzzy system can provide a better evaluation system than classical systems. © 2014 IEEE.
Keywords: assessment; decision support system; engineering education; fuzzy logic; laboratory applications; peer assessment; student performance